Hic‐5 deficiency protects cerulein‐induced chronic pancreatitis via down‐regulation of the NF‐κB (p65)/IL‐6 signalling pathway. Issue 2 (3rd December 2019) - Chen, Hao; Tan, Peng; Qian, Baolin; Du, Yichao; Wang, Ankang; Shi, Hao; Huang, Zhiwei; Huang, Shiyao; Liang, Tiancheng; Fu, Wenguang
Abstract: Chronic pancreatitis (CP), characterized by pancreatic fibrosis, is a recurrent, progressive and irreversible disease. Activation of the pancreatic stellate cells (PSCs) is considered a core event in pancreatic fibrosis. In this study, we investigated the role of hydrogen peroxide‐inducible clone‐5 (Hic‐5) in CP. Analysis of the human pancreatic tissue samples revealed that Hic‐5 was overexpressed in patients with CP and was extremely low in healthy pancreas. Hic‐5 was significant up‐regulated in the activated primary PSCs independently from transforming growth factor beta stimulation. CP induced by cerulein injection was ameliorated in Hic‐5 knockout (KO) mice, as shown by staining of tissue level. Simultaneously, the activation ability of the primary PSCs from Hic‐5 KO mice was significantly attenuated. We also found that the Hic‐5 up‐regulation by cerulein activated the NF‐κB (p65)/IL‐6 signalling pathway and regulated the downstream extracellular matrix (ECM) genes such as α‐SMA and Col1a1. Therefore, we determined whether suppressing NF‐κB/p65 alleviated CP by treating mice with the NF‐κB/p65 inhibitor triptolide in the cerulein‐induced CP model and found that pancreatic fibrosis was alleviated by NF‐κB/p65 inhibition. These findings provide evidence for Hic‐5 as a therapeutic target that plays a crucial role in regulating PSCs activation and pancreatic fibrosis.